Reviewing the Advances in Photovoltaic Materials for Solar Energy: A Global Perspective - Ojong Felix Enow; Andrew Tochukwu Ofoedu; Ebimor Yinka Gbabo; Possible Emeka Chima; Oluwapelumi Joseph Adebowale (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
The quest for sustainable and clean energy sources has propelled intense research and development in the field of photovoltaics, aiming to harness solar energy efficiently. This Review reviews the recent advances in photovoltaic materials on a global scale, providing a comprehensive overview of the innovations that hold promise for enhancing the efficiency, durability, and cost-effectiveness of solar energy conversion technologies.The rapid evolution of photovoltaic materials has been driven by the need to address the challenges associated with traditional silicon-based solar cells. This review explores the emergence of novel materials, such as perovskites, organic polymers, and quantum dots, which have exhibited remarkable photovoltaic properties. Perovskite solar cells, in particular, have garnered attention for their low-cost fabrication, ease of scalability, and competitive power conversion efficiencies, heralding a paradigm shift in the solar energy landscape.Moreover, the global perspective presented in this review highlights the collaborative efforts of researchers, industries, and policymakers across diverse regions. Regions such as Asia, Europe, and North America have witnessed significant investments and strategic initiatives aimed at advancing photovoltaic technologies. The exploration of regional approaches and trends offers valuable insights into the diverse strategies employed to propel the adoption of solar energy on a global scale.Furthermore, the review delves into breakthroughs in material engineering, including advancements in thin-film technologies, tandem solar cells, and innovative manufacturing processes. These breakthroughs not only contribute to improving the performance of photovoltaic devices but also pave the way for the integration of solar energy solutions into various applications, from portable electronics to building-integrated photovoltaics.In conclusion, this Review provides a snapshot of the dynamic landscape of photovoltaic materials, showcasing how global research efforts are shaping the future of solar energy. The ongoing innovations in materials science, coupled with collaborative initiatives on an international scale, are pivotal in realizing the full potential of solar energy as a sustainable and ubiquitous power source.